UPAYA GURU BIMBINGAN DAN KONSELING DALAM MEMBANGKITKAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 2 PANGKALAN KURAS KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Awaluddin ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the lack of student motivation. This study aims to increasestudents' motivation. This research is a class act, Based on the results through the processingof the questionnaire, the efforts of guidance teachers to motivate students overall belajarjincluded into the category Good. Based on the collection of data obtained from thequestionnaire to 30 students with 12 questions can be authors conclude that the ultimateanswer is SS (very often). Therefore it can be considered that the guidance teacher efforts tomotivate student learning in SMPN 2 Pangkalan Kuras Kecamatan Pangkalan Kuras "PrettyGood".